2018
DOI: 10.18310/2446-4813.2018v4n2p85-97
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de idosos acompanhados na Estratégia Saúde da Família

Abstract: Objetivo: Avaliar a qualidade de vida de idosos atendidos na Estratégia Saúde da Família de uma capital do nordeste brasileiro. Métodos: Estudo descritivo, de corte transversal, realizado com 89 idosos atendidos em uma Unidade Básica de Saúde de Teresina, Piauí, Brasil. Os critérios de inclusão foram: idade entre 60 e 70 anos e concordar em participar do estudo, assinando o termo de consentimento. Os dados foram coletados através de um questionário com perguntas fechadas, com o objetivo de levantar dados confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Emotional Exhaustion showed a strong positive correlation with Depersonalization, collaborating with the strengthening of the assumption that Emotional Exhaustion leads to Depersonalization, as it is often a defense mechanism for professionals against emotional exhaustion and low personal achievement (35) . Thus, it is necessary to intervene in the aspects that lead to emotional exhaustion to prevent depersonalization and protect the health of workers and the quality of the care provided to the community.…”
Section: Discussionsupporting
confidence: 52%
“…Emotional Exhaustion showed a strong positive correlation with Depersonalization, collaborating with the strengthening of the assumption that Emotional Exhaustion leads to Depersonalization, as it is often a defense mechanism for professionals against emotional exhaustion and low personal achievement (35) . Thus, it is necessary to intervene in the aspects that lead to emotional exhaustion to prevent depersonalization and protect the health of workers and the quality of the care provided to the community.…”
Section: Discussionsupporting
confidence: 52%
“…Scholars have pointed out that social and family factors also modify the quality of sleep. 25 Moreover, they reported that conflicting family relationships can have a negative impact on the physical, social, and emotional health of individuals. In this sense, the sleep of the older adults may be impaired in a dysfunctional context.…”
Section: Discussionmentioning
confidence: 99%
“…A Exaustão Emocional apresentou correlação positiva forte com a Despersonalização, colaborando com o fortalecimento da premissa de que a Exaustão emocional leva à Despersonalização, por ser muitas vezes um mecanismo de defesa dos profissionais contra a exaustão emocional e baixa realização pessoal (35) . Assim faz-se necessário intervir nos aspectos que levam a Exaustão emocional com intuito de prevenir a despersonalização e proteger a saúde dos trabalhadores e a qualidade do serviço oferecido por esses à comunidade.…”
Section: Discussionunclassified